Methodology proposal for spatial analysis of soil nutrients in watersheds - Silva, Darllan Collins da Cunha e; Albuquerque Filho, José Luiz; Oliveira, Renan Angrizani de; Lourenço, Roberto Wagner (Sociedade & Natureza, 2018)
Environmental indices are important information tools about the state of the soil resulting from the use and anthropic management that impacts positively or negatively the quality of life in living beings. The objective of this study was to elaborate aSoil and Environmental Status Index (SESI) to analyze the spatialization through interpolation by ordinary kriging of soil chemical factors resulting from anthropic use and management in the Una River Watershed. Thus, it is possible to observe that there is a phosphorus deficit in the Una River Watershed and that the transport of this nutrient to the water bodies can trigger eutrophication processes. Approximately 65% of the area of the Una River Watershed is classified as regular, that is, they are in the range of 0.38 to 0.60. There were no values classified as bad or awful for the SESI, indicating that the Watershed is poorly degraded, a fact evidenced by the occupation rate by forests in the study area that corresponds to 41% of the territorial extension. The SESI can be used asan important tool for the management of soil state in watersheds, since it allows the interpretation of this state numerically, and can serve as a decision-making tool for public and private managers.